Perputaran Piutang Terhadap Return On Asset pada PT Air Asia Indonesia Tahun 2015-2022 - Khoirunnisa, Rossa; Widiyanti, Wiwik; Islami, Vina (JURNAL MUTIARA AKUNTANSI, 2023)
PT Air Asia Indonesia Tbk is a domestic and international airline with low fares but has a variety of attractive offers and services. This study aims to find out and compare receivables turnover at PT Air Asia Indonesia Tbk against Return On Assets. The research method used is quantitative analysis, processed using statistics to draw general conclusions. The hypothesis in this study is that accounts receivable turnover (X) has a positive effect on return on assets (Y). The data used is secondary data obtained in the form of financial reports received from the official website of the Indonesia Stock Exchange, www.idx.co.id. Furthermore, the data is processed using classical assumption test data analysis, hypothesis, simple linear regression, and the coefficient of determination using SPSS Ver. software. 22. The output of the SPSS conclusion results that Ha is accepted and H0 is rejected. Then, from the test results of the coefficient of determination, it is known that accounts receivable turnover has significantly reduced the return on assets by 41.5%. Thus, it can be interpreted that there is a significant influence on Return On Assets (X) at PT Air Asia Indonesia Tbk.